Interactive effects of diclofenac and copper on bioconcentration and multiple biomarkers in crucian carp (Carassius auratus). (March 2020) - Xie, Zhengxin; Luan, Haiyang; Zhang, Yixuan; Wang, Min; Cao, Danchun; Yang, Jianhao; Tang, Jun; Fan, Shisuo; Wu, Xiangwei; Hua, Rimao
Abstract: Diclofenac (DCF), a non-steroidal anti-inflammatory drug, is widespread in aquatic environments and coexists with heavy metals to form combined pollution. However, the interactive effects of DCF and heavy metals on aquatic organisms remain unknown. This study aimed to investigate the interactive effects of DCF and copper (Cu) on the bioconcentration, oxidative stress status and detoxification-related gene expression in crucian carp ( Carassius auratus ). Fish were exposed to Cu (100 μg L −1 ) and DCF (1, 10, 100 and 1000 μg L −1 ) alone or in combination for 7 days. Results obtained showed that the treatment of Cu combined with high levels of DCF (100 and 1000 μg L −1 ) significantly decreased tissue concentrations of DCF and Cu compared to the correspondingly individual exposure. Concerning oxidative stress status, as reflected by the activities of antioxidant enzymes and malondialdehyde content, low exposure concentrations of DCF (1 and 10 μg L −1 ) seemed to mitigate the oxidative stress induced by Cu, whereas the co-exposure of Cu with the highest level of DCF (1000 μg L −1 ) led to stronger oxidative damage in fish liver than Cu exposure alone. With regarding to detoxification-related genes, in most cases, the expressions of cyp 1a, cyp 3a, gstα, gstπ, pxr and P-gp in crucian carp were significantly altered upon exposure to the compounds in combination compared to exposure to the compounds individually. Collectively, these findings indicate the capacity of each of these pollutants to alter bioconcentration potential, pro-oxidative effects and detoxification-related gene responses of the other when both co-occur at specific concentrations. Graphical abstract: Image 1 Highlights: Interactive effects of DCF and Cu on crucian carp were studied. Alleviated accumulation of DCF and Cu were observed in the combination treatment. Co-exposure to Cu and DCF at high levels provoked severer hepatic oxidative stress. Mixtures changed detoxification related gene expressions compared to individuals.